LEGAL RECONSTRUCTION OF INTELLECTUAL PROPERTY VALUATION INSTITUTIONS AS FIDUCIARY SECURITY TO REALIZE LEGAL CERTAINTY - I. Irfan Ibrahiem; Elfrida Ratnawati; Simona Bustani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The utilization of Intellectual Property (IP) as an economic asset in Indonesia is significantly hampered when applied as fiduciary security due to profound legal uncertainty, particularly surrounding valuation mechanisms. A primary obstacle is the dearth of a standardized, legally recognized IP valuation institution, which inhibits the acceptance of IP as collateral by financial institutions. This study aims to analyze and reconstruct the legal framework governing these valuation institutions to establish legal certainty. Using a normative juridical method with statutory and conceptual approaches, the research identifies key issues: inadequate existing regulations, and the rejection of IP by banks owing to valuation difficulties, value fluctuation risks, and execution uncertainties. The findings conclude that a legal reconstruction of the IP valuation institution is essential. This reconstruction must establish standardized valuation criteria and fortify the legal framework, thereby enabling IP to function as an effective financing instrument and realizing legal certainty in Indonesia.